The microRNA‐200 family—A potential diagnostic marker in hepatocellular carcinoma?. Issue 4 (4th June 2014) - Dhayat, Sameer A.; Mardin, Wolf A.; Köhler, Gabriele; Bahde, Ralf; Vowinkel, Thorsten; Wolters, Heiner; Senninger, Norbert; Haier, Jörg; Mees, Soeren T.
<x xml:space="preserve">Abstract</x> Background Hepatocellular carcinoma (HCC) represents the main cause of death among patients with cirrhotic liver disease, but little is known about mechanisms of cirrhosis associated carcinogenesis. We investigated the diagnostic impact of microRNA‐200 (miR‐200) family members as important epigenetic regulators of epithelial–mesenchymal transition (EMT) to differentiate between patients with HCC and liver cirrhosis. Methods Expression of the miR‐200 family was investigated by qRT‐PCR in specimens of HCC patients with and without cirrhosis. Benign specimens with and without cirrhosis served as controls. Expression of the EMT markers ZEB‐1, E‐cadherin and vimentin was examined using immunohistochemistry. Results MiR‐200a and miR‐200b were significantly downregulated in HCC (miR‐200a: −40.1% (P = 0.0002); miR‐200b: −52.3% (P = 0.0002)), and in HCC cirrhotic tissue (miR‐200a: −40.2% (P = 0.004); miR‐200b: −51.1% (P = 0.007)) compared to liver cirrhosis. Spearman's Rho analysis revealed a significant negative correlation of miR‐200a and miR‐200b to the expression of the mesenchymal markers Vimentin (P < 0.007) and ZEB‐1 (P < 0.0005) and a significant positive correlation to the epithelial marker E‐cadherin (P < 0.0002). Conclusions MiR‐200 family members and their targets are significantly deregulated in HCC and liver cirrhosis. The miR‐200 family is able to distinguish between cirrhotic and HCC tissue and could serve as an early marker for cirrhosis‐associated HCC. J. Surg. Oncol. 2014; 110:430–438. © 2014 Wiley Periodicals, Inc.